Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2174/1381612828666220601153426
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Activities of Dietary Phytoestrogens against Prostate Cancer: From Observational to Clinical Studies

Abstract: Prostate cancer remains one of the most frequent and deadliest malignancies in males, where the rate of disease progression is closely associated with the type of dietary intake, specifically Western-style diet. Indeed intake of the Asian diet, which contains abundant phytoestrogens, is inversely correlated with a higher risk of prostate cancer, suggesting a chemoprotective effect of phytoestrogen against cancer progression. Although the role of phytoestrogens in cancer treatment was well documented, their imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 195 publications
0
11
0
Order By: Relevance
“…These natural agents can target several BC‐related pathways and provide protective activity against breast malignancies, which play a significant role in preventing and managing patients with BC 46,49 . Several individual studies exhibited phytochemicals had anti‐cancer property through several mechanisms 50–52 . However, a comprehensive summary on precise anti‐cancer mechanisms including apoptosis induction, cell cycle, and cell proliferation regulation, inhibition of angiogenesis and metastasis, regulating hypoxia‐inducible factor, suppressed mammosphere formation, onco‐inflammation inhibition, controlling enzyme activity, signal transduction regulation, epigenetic and immune regulation have not been reported collectively.…”
Section: Introductionmentioning
confidence: 99%
“…These natural agents can target several BC‐related pathways and provide protective activity against breast malignancies, which play a significant role in preventing and managing patients with BC 46,49 . Several individual studies exhibited phytochemicals had anti‐cancer property through several mechanisms 50–52 . However, a comprehensive summary on precise anti‐cancer mechanisms including apoptosis induction, cell cycle, and cell proliferation regulation, inhibition of angiogenesis and metastasis, regulating hypoxia‐inducible factor, suppressed mammosphere formation, onco‐inflammation inhibition, controlling enzyme activity, signal transduction regulation, epigenetic and immune regulation have not been reported collectively.…”
Section: Introductionmentioning
confidence: 99%
“…The NCI began a screening trial for plant‐based anticancer drug development in 1960, and more than 50–70% of the anti‐cancer drugs are generated from natural compounds (Sak, 2022; Sohel et al, 2023). This is because plant‐based compounds with natural properties could be a safe and efficient treatment method for managing various types of human cancer (Sohel, Sultana, et al, 2022; Solowey et al, 2014). Although the choice between using phytochemicals for cancer prevention depends on various factors, including the specific disease, individual health goals, and available evidence; however, phytochemicals possess a wide range of therapeutic advantages like natural source, lower risk of side effects, lifestyle benefits, nutrient synergy, seasonal availability, and low cost (Monjotin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although the choice between using phytochemicals for cancer prevention depends on various factors, including the specific disease, individual health goals, and available evidence; however, phytochemicals possess a wide range of therapeutic advantages like natural source, lower risk of side effects, lifestyle benefits, nutrient synergy, seasonal availability, and low cost (Monjotin et al, 2022). There are numerous anticancer mechanisms in phytochemicals, including anti‐inflammatory (Sahin et al, 2021), antiproliferative (Biswas et al, 2022; Choudhari et al, 2020), arresting cell cycle (Singh et al, 2002; Sohel, Biswas, et al, 2022), apoptosis regulation (Patra et al, 2021; Sohel, Islam, et al, 2022), anti‐invasive (Orloff et al, 2016), antimetastatic (Choudhari et al, 2020; Morshed et al, 2023; Sohel, Sultana, et al, 2022), and antiangiogenic properties (Choudhari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, phytochemicals can influence cell growth and survival, metastasis, angiogenesis, apoptosis, and oncogene inactivation in a variety of in vitro and animal models 14–17 . Although the intrinsic signaling pathways targeted by phytochemicals in cancer treatment of cancer is still unknown, previous studies have shown that they can suppress both the STAT NF‐B, PIK/AKT, and MAPK signaling pathways and activate some genes that are responsible for tumor suppressor activity in a variety of cancer models 18 . Furthermore, some commonly used anti‐cancer medications, such as Taxol, resveratrol, vincristine, quercetin, vinblastine, tetrandrine, and arteannuin for multiple malignant tumors, are made from natural substances 19 .…”
Section: Introductionmentioning
confidence: 99%